Cephalometric Measurements of Upper Airway at Upright and Supine Posture in Adult OSAS Patients - Ng, Chun Hown; Chu, Guang; Gu, Min; Leung, Yiu Yan; Lin, Lizhuo; Yang, Yanqi (European Journal of Dentistry, 2025)
This article aims to investigate whether posture (upright vs. supine) affects airway-related cephalometric measurements in adult Chinese patients with obstructive sleep apnea syndrome (OSAS).Twenty-seven adult Chinese male patients with OSAS (mean age, 50.1 ± 10.2 years), diagnosed through polysomnography, were recruited. All of the recruited patients had their lateral cephalograms taken in the upright posture and lateral cephalometric images taken using spiral computed tomography scans in the supine posture within a 3-month interval. Healthy Chinese men were included as the control group. Fourteen cephalometric parameters were measured using the images of the upper airway and craniofacial structures taken in the upright and supine postures.A paired Student's t-test was applied to assess the differences between the two radiographic images, with statistical significance defined as p < 0.05.Significant differences were observed in the distance between the tip of the soft palate and the posterior pharyngeal wall, tongue length, tongue height, and hyoid bone (p < 0.05). These findings indicate that when the body posture was changed from upright to supine, the hyoid bone moved inferiorly and in the forward direction and the soft palate and tongue became thicker and shorter. No statistically significant difference was observed in the narrowest pharyngeal airway space between the upright and supine postures (p > 0.05).Posture mainly affects the cephalometric measurements of the soft palate and tongue and the hyoid bone position. PASmin and U-MPW can still serve as reliable markers in upright lateral cephalometric radiographs for early detection of OSAS.
Keywords: obstructive sleep apnea; Chinese; supine; upright; posture